Milk yield and quality of dairy cows transitioning from milking parlour to automatic milking system - Luca Crocco; Silvia Magro; Angela Costa; Mauro Penasa; Massimo De Marchi (Italian Journal of Animal Science)
This study investigated the effects of changing from milking parlour (MP) to automatic milking system (AMS) on test-day milk yield and quality traits of dairy cows, using data from 2012 to 2024. Only cows present in both milking systems were considered. Two datasets were available: (i) a single-breed set (38,290 test-day records from 1463 Holstein cows in 31 herds) and (ii) a multi-breed set (8892 test-day records from 403 Holstein, Brown Swiss, and Simmental cows in 11 herds). A linear mixed model was applied, accounting for fixed effects of parity, lactation stage, milking system, and their interactions. Random effects of cow and herd-test-day were included. In multi-breed data, breed and milking system × breed were also added. Holstein cows in single-breed herds yielded 1.40 kg/d more milk in AMS than MP, especially in primiparous cows. However, AMS milked cows had higher somatic cell count (SCC), urea concentration, and pH, with a lower casein index. In multi-breed herds, milk yield differences between systems were not statistically significant. Across breeds, the casein index was lower in AMS than MP. Then, SCC was treated as binary trait (≤ and > 200,000 cells/mL) and logistic regression was performed using the models described above. Holstein cows milked with AMS were more likely to have SCC >200,000 cells/mL, with no such differences in other breeds. Even if switching to the AMS results in increased milk yield, it leads to a deterioration of milk quality, suggesting that the transition is a stressor for the cows.